Economics : the user's guide - Chang, Ha-Joon. (New York, NY : Bloomsbury Press, 2014)
"Unlike many economists, who present only one view of their discipline, Chang introduces a wide range of economic theories--from the Classical economists to the Behavioral economists, from the Marxists to the Austrians--revealing how each has its strengths and weaknesses and why there is no one correct way to explain economic behavior. Instead, by challenging received wisdom and exposing the myriad institutional, political, and technological forces that shape our economic world, Chang explains how our increasingly global and interconnected world works and is evolving. Economics: The User's Guide is a concise and expertly crafted guide to economic theories, and will give all who read it a clear and accurate picture of the global economy and how and why it affects our daily lives."--Jacket.
Prologue. Why bother? : why do you need to learn economics? -- How to read this book -- Part 1. Getting used to it. Life, the universe, and everything : what is economics? -- From pin to PIN : capitalism 1776 and 2014 -- How have we got here? : a brief history of capitalism -- Let a hundred flowers bloom : how to 'do' economics -- Dramatis personae : who are the economic actors? -- Moving on ... -- Part 2. Using it. How many do you want it to be? : output, income and happiness -- How does your garden grow? : the world of production -- Trouble at the Fidelity Fiduciary Bank : finance -- Boris's goat should drop dead : inequality and poverty -- I've known a few people who've worked : work and unemployment -- Leviathan or the philosopher king? : the role of the state -- 'All things in prolific abundance' : the international dimension -- Epilogue. What now? : how can we use economics to make our economy better?
"First published in Great Britain in 2014"--Title page verso.
Includes bibliographical references and index.
Keywords: Economics